2003
DOI: 10.1104/pp.102.014936
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylethanolamine Signaling in Tobacco Is Mediated by a Membrane-Associated, High-Affinity Binding Protein

Abstract: N-Acylethanolamines (NAEs) are fatty acid derivatives found as minor constituents of animal and plant tissues, and their levels increase 10- to 50-fold in tobacco (Nicotiana tabacum) leaves treated with fungal elicitors. Infiltration of tobacco leaves with submicromolar to micromolar concentrations ofN-myristoylethanolamine (NAE 14:0) resulted in an increase in relative phenylalanine ammonia-lyase (PAL) transcript abundance within 8 h after infiltration, and this PAL activation was reduced after co-infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…However, activation of defense-signaling cascades in plants is a consequence of sensing of the elicitor by specific plant receptors (Tripathy et al 2003). Since harpin-induced HR is a potentially useful tool for conferring pathogen-resistance on selected plants, transformation with harp genes has been used to engineer pathogen-resistance (Keller et al 1999;Peng et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, activation of defense-signaling cascades in plants is a consequence of sensing of the elicitor by specific plant receptors (Tripathy et al 2003). Since harpin-induced HR is a potentially useful tool for conferring pathogen-resistance on selected plants, transformation with harp genes has been used to engineer pathogen-resistance (Keller et al 1999;Peng et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…phenylalanine ammonia-lyase and PAL2 transcript abundance) in tobacco plants within hours of treatment in a manner similar to but independent of elicitor proteins (17). Mammalian cannabinoid receptor antagonists at concentrations equimolar to NAE blocked the activation of defense gene expression induced by either NAEs or by fungal elicitor proteins (16). A membrane-associated protein was identified in leaves of tobacco (and other plant species), which specifically bound to [ 3 H]NAE 14:0 with high affinity (K d in the low nanomolar range).…”
mentioning
confidence: 99%
“…A membrane-associated protein was identified in leaves of tobacco (and other plant species), which specifically bound to [ 3 H]NAE 14:0 with high affinity (K d in the low nanomolar range). This NAE 14:0-binding protein was proposed to mediate the NAE activation of PAL2 expression in tobacco leaves, a conclusion that was based on the similarities between NAE binding properties in vitro and NAEinduced physiological responses in vivo, including experiments with cannabinoid receptor antagonists (16). Although some clear differences are evident between the emerging NAE signaling pathway in plants and the better characterized endocannabinoid signal pathway of animals, there appear to be some remarkable similarities in the formation and perception of bioactive acylethanolamides by these two diverse groups of multicellular organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional enzyme studies showed that NAE could be metabolized to free fatty acids and ethanolamine (EA) by an amide hydrolase . In plants, NAPE-NAE metabolism is involved in PLD-mediated accumulation of NAE14:0 following elicitor perception, in NAE14:0 activation of phenylalanine ammonia lyase gene expression independent of pathogen elicitors, and in NAE14:0 reduction of pathogeninduced alkalinization (Tripathy et al 1999(Tripathy et al , 2003. These authors suggest that metabolism of NAPE and the specific accumulation of NAE14:0 is part of a transduction pathway that modulates cellular defence responses following perception of fungal elicitors.…”
Section: N-acyl-phosphatidylethanolamine and N-acylethanolaminementioning
confidence: 87%